Classification of dry and wet macular degeneration based on the ConvNeXT model - Wu, Maonian; Lu, Ying; Hong, Xiangqian; Zhang, Jie; Zheng, Bo; Zhu, Shaojun; Chen, Naimei; Zhu, Zhentao; Yang, Weihua (Frontiers in Computational Neuroscience, 2022)
Purpose: To assess the value of an automated classification model for dry and wet macular degeneration based on the ConvNeXT model. Methods: A total of 672 fundus images of normal, dry, and wet macular degeneration were collected from the Affiliated Eye Hospital of Nanjing Medical University and the fundus images of dry macular degeneration were expanded. The ConvNeXT three-category model was trained on the original and expanded datasets, and compared to the results of the VGG16, ResNet18, ResNet50, EfficientNetB7, and RegNet three-category models. A total of 289 fundus images were used to test the models, and the classification results of the models on different datasets were compared. The main evaluation indicators were sensitivity, specificity, F1-score, area under the curve (AUC), accuracy, and kappa. Results: Using 289 fundus images, three-category models trained on the original and expanded datasets were assessed. The ConvNeXT model trained on the expanded dataset was the most effective, with a diagnostic accuracy of 96.89%, kappa value of 94.99%, and high diagnostic consistency. The sensitivity, specificity, F1-score, and AUC values for normal fundus images were 100.00%, 99.41%, 99.59%, and 99.80%, respectively. The sensitivity, specificity, F1-score, and AUC values for dry macular degeneration diagnosis were 87.50%, 98.76%, 90.32%, and 97.10%, respectively. The sensitivity, specificity, F1-score, and AUC values for wet macular degeneration diagnosis were 97.52%, 97.02%, 96.72%, and 99.10%, respectively. Conclusion: The ConvNeXT-based category model for dry and wet macular degeneration automatically identified dry and wet macular degeneration, aiding rapid and accurate clinical diagnosis.